IMPLEMENTASI SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI PEMBUANGAN SAMPAH LEGAL BERBASIS WEBSITE DI KOTA BANDAR LAMPUNG - Rahardi, Agus; Estian Pambudi, Randi; Septiawan, Yuda; Ade Muktiawan, Danang; Irfan, Muhammad (LP2M Institut Informatika Dan Bisnis Darmajaya, 2024)
Waste disposal that is not well managed in Bandar Lampung City caused problems with a negative impact on the environment and public health. Lack of related information legal dump sites make things difficult for cleaning crews, leading to dumping carelessness and increasing the risk of health problems. Official local government websites were not yet optimal in providing information, giving rise to the need for more effective solutions. This research aims to implement a Geographic Information System (GIS) for mapping legal waste disposal locations in Bandar Lampung City via its website. The research focused only on legal waste and mapping its location. The data used comes from environmental services and other supporting sources. The results are expected to make things easier for cleaning officers to access information, increase the effectiveness of waste management, assist government decision-making, increase the efficiency of waste management, environmental cleanliness and transparency. With more complete and accurate information, it is hoped that waste management will become more planned and coordinated and provide a platform for data and information related to legal waste disposal locations. Furthermore, community empowerment can be carried out for more sustainable research results in location mapping and integration with others system to improve overall waste management more efficient.